The Privatization process in Russia, Ukraine, and the Baltic States : economic environment, legal and ownership structure, institutions for state regulation, overview of privatization programs, initial transformation of enterprises - Frydman, Roman, 1948- (CEU privatization reports ;, 1993)
In this work, comprehensive comparative information on five former Soviet republics has been collected by teams of researchers from both within the region and from the West. Following an introduction to the economic environment in each country, it provides an overview of the privatization process, including an account of the legal framework of ownership, institutions for state regulation, an overview of privatization programmes and the initial transformation of enterprises. A key feature of the book is the authors' access to hitherto unavailable information and their ability to present a vast amount of material in an easily available format. Aimed at policy makers and business people, the work should provide a strong foundation for future research.